PENGARUH PERSEPSI SISWA TENTANG KOMPETENSI GURU TERHADAP HASIL BELAJAR GAMBAR TEKNIK DAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR GAMBAR TEKNIK SISWA KELAS XI DI SMK N 3 YOGYAKARTA - Arga Kuncoro Jati; Sukaswanto Sukaswanto (Jurnal Pendidikan Vokasi Otomotif, 2021)
This study aims to determine (1) The Influence of Students' Perceptions About Teacher Competence on Technical Drawing Learning Outcomes, (2) The Effect of Student Learning Interest on Learning Outcomes of Technical Drawing of Class XI Light Vehicle Engineering Students at SMK N 3 Yogyakarta 2018/2019 school year. The subjects of this study were all students of class XI of Light Vehicle Engineering at SMK N 3 Yogyakarta, totaling 71 students. Data collection using a questionnaire, for Student Perceptions About Teacher Competence and Student Learning Interest in Technical Drawing Subjects and Student Learning Outcomes Class XI teaching 2018/2019. The trial of the research instrument was conducted at SMK N 3 Yogyakarta on 32 students of class X TKR 2. The analysis requirements test included the linearity and normality of each variable. Hypothesis testing uses the results of r and t tests. The results of this study are: (1) Students' Perceptions of Teacher Competence (X1) have a positive effect on Student Learning Outcomes (Y) of 0.135. This shows the more positive the Student's Perception about Teacher Competence, the higher the Learning Outcomes (2) Student Learning Interest (X2) has a positive effect on Learning Outcomes (Y) of 0.096. This shows the higher the Student's Interest in Learning, the higher the Learning Outcomes.